Parallel processing and applied mathematics : 12th International Conference, PPAM 2017, Lublin, Poland, September 10-13, 2017, Revised selected papers.: 12th International Conference, PPAM 2017, Lublin, Poland, September 10-13, 2017, Revised selected papers. Part I (2018) - Unknown
No abstract available